Primary hyperthyroidism complicated by primary hyperparathyroidism: a case report and literature review - Guo, Hongpeng; Lv, Jie; Zhang, He; Li, You; Pan, Xinghe; Zhang, Junjie; Sun, Chenglin (Frontiers in Oncology, 2025)
BackgroundThe clinical occurrence of primary hyperthyroidism (PH) combined with primary hyperparathyroidism (PHPT) is exceedingly rare. There remains considerable debate regarding the necessity of iodine use prior to surgery for hyperthyroidism and whether thyroid function should be normalized before proceeding with the operation. Furthermore, the decision on whether to perform total parathyroidectomy or subtotal parathyroidectomy due to parathyroid hyperplasia must be based on a comprehensive assessment by a multidisciplinary team (MDT).Case presentationHerein, we report a rare case of concurrent PH, caused by Graves’ disease(GD), and PHPT. Through the collaboration of a MDT, we developed a personalized preoperative preparation and surgical plan for the patient, successfully managing the postoperative complications.ConclusionClinicians should maintain a high level of suspicion for PHPT in hyperthyroid patients with hypercalcemia. Additionally, the decision regarding the preoperative use of iodine, the normalization of thyroid function before surgery, and the surgical approach to parathyroid hyperplasia should be determined through effective preoperative assessment, imaging studies, and MDT collaboration. This strategy allows for the formulation of individualized treatment plans, mitigating the risks of postoperative hyperthyroid crises, recurrence of PHPT, and permanent parathyroid insufficiency.